COVID-19 vaccine and the risk of flares in inflammatory arthritis: a systematic literature review and meta-analysis - Hoxha, Ariela; Striani, Giovanni; Lovisotto, Marco; Simioni, Paolo; Doria, Andrea; Ramonda, Roberta (Frontiers in Immunology, 2024)
Introduction. Coronavirus disease 2019 (COVID-19) vaccines aroused concerns about the risk of flares and adverse events in inflammatory arthritis (IA) since the vaccine clinical trials did not specifically investigate this subset of patients.A systematic literature review and meta-analysis to summarize the data on joint disease flare and adverse events following immunization (AEFI). Two researchers independently evaluated the literature on Pubmed, Scopus, and EMBASE databases from 22 nd March 2020 to 30 th September 2023. A random-effects model was used to pool odds ratios (OR) (with 95% CI) for the risk of joint disease flares and adverse events. Subgroup analyses were performed to evaluate the risk of disease flare between different IA and adverse events.Heterogeneity was assessed by I 2 statistic.Results. A total of 9874 IA patients were included in the study: 6579 (66.6 %) patients affected by RA and 3295 (33.4 %) spondyloarthritis (SpA). The overall rate of flares was higher in RA vs. SpA (9.1% vs. 5.3%). However, the pooled estimated analysis showed no increased risk of joint disease flare following COVID-19 vaccination in patients affected by RA vs. SpA [OR 0.88, 95% CI: 0.77-1.00]. Furthermore, a subgroup analysis showed an increased risk of joint flares in psoriatic arthritis (PsA) patients vs. RA [OR 0.79, p=0.004]. The pooled estimated analysis revealed no increased risk of AEFI in patients with RA vs. SpA [1.02, 95% CI: 0.63-1.65]. Conclusions. Our meta-analysis summarized the current evidence on joint disease flares and COVID-19 vaccine-associated AEFI in IA patients. Pooled analysis showed an increased risk of disease flares in PsA vs. RA patients.